Determination Of Activity Relationship Chart (ARC) Method in Evaluation Of Office Layout (Case Study on Hotels & Apartments XYZ Bandung) - Tejaningrum, Ayi; Hasna, Gita Muthia (International Journal of Applied Business and International Management, 2024)
Layout design is a physical arrangement that regulates the flow of materials, information, and human relationships.XYZ Bandung Apartment has 12 departments located on the lobby floor to the fourth basement floor. The company has an office layout that is still not optimally organized, such as the placement of departments that are far apart, ineffective handling of goods and the risk of work accidents. The purpose of this study is to improve the existing layout so that the results of the comparison between before and after the repair will be seen. The research method is a survey where employee and management preferences are the reference in determining close relationships. The research method is a survey, with the analysis tool used is ACV (Activity Relations Chart) where employee and manager preferences are the reference in determining close relationships. The selected sample was 56 people consisting of management and employees. Based on the results of the analysis, there were changes in department placement resulting in an efficiency of travel distance between sections of 64.3% and time efficiency of 64.4%. Several proposed changes related to the relocation of less important departments and relatively low frequency of relationships